2019
DOI: 10.3389/fpls.2019.00679
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Developmental Arrest: Maintaining Pollen Fertility in a World With a Changing Climate

Abstract: During evolution of land plants, the haploid gametophytic stage has been strongly reduced in size and the diploid sporophytic phase has become the dominant growth form. Both male and female gametophytes are parasitic to the sporophyte and reside in separate parts of the flower located either on the same plant or on different plants. For fertilization to occur, bi-cellular or tri-cellular male gametophytes (pollen grains) have to travel to the immobile female gametophyte in the ovary. To survive exposure to a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 188 publications
(235 reference statements)
4
65
0
1
Order By: Relevance
“…Many factors influence pollen germination: time of collection, the season, conditions of pollen storage and others. The obtained results indicated that this trait is under the strong influence of ecological factors, which was previously reported for other fruit species [35,38]. In this study, it was particularly pronounced in the cultivar "Conference", which showed the highest difference in pollen germination in vitro between two years.…”
Section: Pollen Germination In Vitrosupporting
confidence: 83%
“…Many factors influence pollen germination: time of collection, the season, conditions of pollen storage and others. The obtained results indicated that this trait is under the strong influence of ecological factors, which was previously reported for other fruit species [35,38]. In this study, it was particularly pronounced in the cultivar "Conference", which showed the highest difference in pollen germination in vitro between two years.…”
Section: Pollen Germination In Vitrosupporting
confidence: 83%
“…High temperatures affect grain yield with up to 50% yield loss, which can be caused by a variety of mechanisms (22)(23)(24)(25)(26)(27). Heat can reduce seed set by accelerating plant development, causing asynchrony between male and female gamete development as well as reducing ovary and pollen viability (28)(29)(30). Accelerated development during grain-fill reduces the time available for seed storage molecule accumulation (6).…”
Section: Discussionmentioning
confidence: 99%
“…2L and 7). Second, Pacini et al [44] indicated that anther stomata may play a crucial role in anther dehydration in rice, which may favor anther dehiscence and pollen shedding. Recently, in ICE1 (ice1-2) Arabidopsis mutants, Wei et al [45] found that decreased stomata density and abnormal stomata development were not advantageous for anther dehydration and anther water movement, so the epidermis did not shrink to dehisce, regardless of the existence of stomium cells in the anther; these changes resulted in low pollen dehiscence, low pollen viability and a low germination percentage.…”
Section: The Relationship Of Pollen Viability With Anther Characterismentioning
confidence: 99%